Use of the Robson classification to assess caesarean section trends in tertiary hospital - Gomathy E., Gomathy; Radhika, Kondareddy; Kondareddy, Triveni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: With caesarean sections on the rise WHO proposes that health care facilities use the Robson’s 10 group classification system to audit their C-sections rates. This classification would help understand the internal structure of the CS rates at individual health facilities identify key population groups, indications in each group and formulate strategies to reduce these rates. Methods: This was a cross sectional study for a period of 6 months at a tertiary care hospital in a rural area in Karnataka, South India. Women who delivered during this period were included and classified into 10 Robson’s classes and percentages were calculated for the overall rate, the representation of groups, contribution of groups and Caesarean percentage in each group. Results: Highest contribution was by Group 5 and Group 2. Together these two groups contributed to 50.3% of the total Caesareans. Followed by Group 1 and 10. A Groups 6, 4, 8 and 9 by themselves did not contribute much but within their groups had a 100% C-section rate. Conclusions: Robson 10-group classification provides easy way in collecting information about Caesarean section rate which obtains good insight into certain birth groups. Reducing primary section rates, adequate counselling and encouraging for VBAC, changing the norms for non-reassuring fetal status, training and encouraging obstetricians to perform versions when not contraindicated could reduce the contribution of Robson’s groups towards the absolute C-Section rates.